THE RELATIONSHIP BETWEEN CAREER LADDER AND NURSES JOB SATISFACTION AT A HOSPITAL - Ekawati Saputri; Syahrir A Pasinringi; Julianus Ake (Universitas Airlangga, 2021)
Background: Career ladder is given to nurses to encourage and maintain professional development and practice of nursing. Career ladder has an impact on raising clinical levels, promotion opportunities, competency complexity, rewards and recognition. In this study, the career ladder has started by mapping and conducting, credentials and competency assessment at the levels of pre Nurse Clinicians, Nurse Clinicians Level I and Nurse Clinicians Level II. Almost half of the nurses were dissatisfied (47.2%) with their career development.Aims: This study was to analyzed the relationship between the career ladder and nurses’ job satisfaction.Methods: This study was a quantitative correlational study with a cross-sectional approach. There were 108 nurses as samples selected using consecutive sampling techniques. These respondent who met the inclusion criteria came from Inpatient Room, (i.e VVIP, VIP, Class I, Class 2/3, Ophthalmology Inpatient), Polyclinic, Chemotherapy Unit, NICU (Neonatal Intensive Care Unit), ICU (Intensive Care Unit), Hemodialysis, Emergency room and COT (Centra Operation Theater). Data were analyzed using the Spearman test.Results: There was a significant relationship between career ladder (p=0.000) and nurse’ job satisfaction. The nurse were satisfied with her career development related to implementation of career ladder. Besides, career ladder allowed to be promoted as the heads of the rooms. Rewards and recognition of nurses’ competencies through job promotion affected nurses’ satisfaction.Conclusion: Career ladder affects nurse satisfaction. Nurses can advance their careers through a career promotion, competencies, rewards and recognition from other health professionals. Support from nurse manager is needed as a form of mentoring and evaluation of nurse performance in the career ladder. Keywords: career ladder, job satisfaction, nurses